Nollywood as the Centre of African Cinema and the Reach of its Film Diplomacy: A Comparative Reading Against Hollywood, Bollywood, and the Korean Wave - Meyta Saraswaty Putri (CV. Publikasi Indonesia, 2026)
Nollywood, the Nigerian film industry, releases close to 2,500 titles a year and ranks second in the world by output, behind India and ahead of the United States in some years. How far has Nollywood become the center of filmmaking in Africa, and how does the film diplomacy it carries travel to global audiences? The study draws on Joseph Nye on soft power, Daya Kishan Thussu on media contra-flow, and Simon Anholt on nation branding, and it uses Michael Porter's value chain and diamond model as business tools to read Nollywood as a commercial system and a diplomatic instrument at once. The design is mixed methods. A qualitative comparative case study sets Nollywood against Hollywood, Bollywood, and the Korean Wave, and a quantitative layer reads industry indicators and the Brand Finance Global Soft Power Index across the four countries. The finding is twofold. Nollywood already anchors African cinema by volume, distribution reach, and continental cultural pull, so the first answer is clear. Its diplomacy, by contrast, works mostly through market-driven diffusion rather than a coordinated state programme. The quantitative reading sharpens this: Nigeria produces the most films of the four yet sits 77th on the 2025 Soft Power Index, while Korea, producing far fewer titles, sits 12th, which shows that raw output does not convert into measured influence without orchestration. That organic character gives Nollywood standing as a Global South voice, yet it leaves the diplomatic value under-used next to Korea's governed model.